PEMANFAATAN KREDIT MIKRO PERUMAHAN BAGI MASYARAKAT BERPENGHASILAN RENDAH DI BMT MITRA KHASANAH KOTA SEMARANG - Esariti, Landung; Nirwanto, Anang (Diponegoro University, 2008)
Since 2006, government has started to launch the housing micro finance system for low incomehousehold, and has been implemented in Jakarta, Semarang, Solo and other big cities. In Semarang, thehousing micro finance is used for early home construction and home renovation. This research is todefine the contribution between two implementation of housing micro finance and BMT Mitra Khasanahis selected as a case study. This investigation used the triangulation method, and is supported with theusing of dicriminant technique analysis, scoring and frequency distribution. About 17 respondent areinterviewed, and they have been facilitated by BMT Mitra Khasanah.The research reveals that 83% of housing micro finance application in Genuk is for home renovation,while 17% is for early home construction. There are 3 dominant factors influenced the applicatio;,namely the economy, installment ability and home condition. The results shows that the applicationwould be very useful if there have been an initation to facilitate the low income household in technicaland managerial assistance.